Willingness toward donation in Mexico and the influence of personality - Gonzalez Cruz, Daniela C.; E. Elizondo Omaña, Rodrigo; Quiroga Garza, Alejandro; Martinez Garza, Javier H.; De la Fuente Villarreal, David; De la Garza Castro, Oscar; Guzman Avilan, Katia; Gutiérrez de la O, Jorge; Guzman Lopez, Santos (Sociedad Anatómica Española, 2023)
Organ and body donation are key elements in health sciences. This study examines the perception of the population toward organ and body donation and how it may be influenced by personality traits. A cross-sectional study was designed, in which a questionnaire including items of demographic data and attitudes toward organ and body donation were distributed among the general population. A validated questionnaire for the screening of personality disorders was applied as well. 202 questionnaires were obtained, 76 (37.6%) from men and 126 (62.4%) from women. A total of 95.2% of women and 93.4% of men responded to be in favor of organ donation (p>0.05). However, only 40.3 % of women and 37.8% of men were in favor of body donation. Sixty-eight percent of participants had a probable personality disorder. Of those against body donation, 67% had a probable personality disorder. Body donation is not a well-known option among the Mexican population. However, for a program to be feasible, it is necessary to raise public awareness regarding donation and its implications to achieve greater engagement.